Innovative technologies in the educational process: trends, prospects of development - NataliyaV. Vladimirovna Ageenko; Dariya D. Dorofeeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
To increase the effectiveness of the learning process the necessity to introduce innovative educational technologies is being actualized. Solving this problem contributes to the creation of a virtual educational environment. In order to prove the relevance of using this method, the application of VR models as a new direction in the industry of modern technologies is considered and statistical data of various foreign and Russian consulting companies are provided. The analysis of the development of Russian VR technologies market in three segments: high-level, middle-level, low-level is given, which leads to the conclusion about the dynamics and prospects of its development. Advantages of using this information technology, contributing to a full immersion in the professional environment, are emphasized. The authors come to the conclusion about the advisability of using virtual reality technologies in the educational process.